Hijacking the Chromatin Remodeling Machinery: Impact ofSWI/SNFPerturbations in Cancer - Bernard E. Weissman; Karen E. Knudsen (2009)
Abstract There is increasing evidence that alterations in chromatin remodeling play a significant role in human disease. The SWI/SNF chromatin remodeling complex family mobilizes nucleosomes and functions as a master regulator of gene expression and chromatin dynamics whose functional specificity is driven by combinatorial assembly of a central ATPase and association with 10 to 12 unique subunits. Although the biochemical consequence of SWI/SNF in model systems has been extensively reviewed, the present article focuses on the evidence linking SWI/SNF perturbations to cancer initiation and tumor progression in human disease. [Cancer Res 2009;69(21):8223–30]